FOOD BORNE DISEASES: A NEGLECTED PUBLIC HEALTH CHALLENGE IN PAKISTAN - Shah, Syed Humayun (Journal of Ayub Medical College Abbottabad, 1999)
Foodborne transmission of pathogenic and toxigenic microorganisms has been a recognized hazard for decades. The dangers of botulism from underprocessed canned foods: staphylococcal poisoning from unrefrigerated cream-filled pastries, sliced ham. meat, and poultry salads; and salmonellosis from infected animal products were known even half century ago. Despite new protective measures, changes in preservation techniques and failure to follow recognized procedures have created new dangers. Every year, foodborne infections cause millions of illnesses and thousands of deaths: most infections go diagnosed and unreported Although outbreaks make the news, most foodborne infections occur as individual or sporadic cases. Therefore, the sources of sporadic cases must also be investigated and understood. In the developed world substantial progress has been made in preventing foodborne diseases. For example, typhoid fever, extremely common at the beginning of the 20th century, is now almost forgotten in the United States. It was conquered in the preantibiotic era by disinfection of drinking water, sewage treatment, milk sanitation and pasteurization, and shellfish bed sanitation. Similarly, cholera, bovine tuberculosis, and trichinosis have also been controlled in the US